Psychiatry and the Law : Basic Principles - Wasser, Tobias (Springer International Publishing : Imprint: Springer, 2017)
This book is specifically designed for new psychiatrists and all other medical professionals who lack the legal training necessary to confront ethical issues in the face of the judicial system. Written by experts in the field, each chapter begins with a challenging case vignette synthesized from a historical legal case that places the reader in the role of the treatment administrator. The text presents details of the legal case, historical significance, and the precedent it sets before discussing the core principles of that particular subject area. Each chapter reviews the existing literature and reinforces the most salient points. Topics include risk assessment, substance misuse and the law, issues with child and adolescent psychiatry in the courtroom, prescription medication considerations, and other challenges that are not often adequately addressed in training. The text is specifically designed for new psychiatrists and other professionals who are transitioning from their studies into clinical practice, concisely explaining and defining the issues in a practical, reader-friendly tone suitable as both a quick-reference in a busy environment or as a resource for private study. Forensic Psychiatry: Basic Principles is an excellent resource for new psychiatrists, psychologists, social workers, students, and other professionals accommodating medical and correctional boundaries in practice.
Keywords: Medicine.; Forensic medicine.; Public health.; Psychiatry.; Pharmacotherapy.; Clinical psychology.; elektronické knihy; electronic books